KOMUNIKASI PEMBANGUNAN INFRASTRUKTUR JALAN DI DESA SITU UDIK KECAMATAN CIBUNGBULANG - Permatasari , Siska; Noer Taufik, Rachmi Fidhara; Hidayat, Muhammad Mamduh; El Raihan, Zulham; Nursyifa Khan, Fazal (Fakultas Ilmu Dakwah dan Komunikasi, 2024)
This research is motivated by the many aspirations of the community in fulfilling development needs. The infrastructure development that occurred in Situ Udik Village was a development planned by the village government and its community through deliberation. This research focuses on communication about road infrastructure development in Situ Udik Village, Cibungbulang District. The aim of this research is to find out how communication works for road infrastructure development in Situ Udik Village, Cibungbulang District. Development Communication includes the role and function of communication between all parties involved, especially the community and the government from the planning process, implementation to evaluation. In this research, the author used a qualitative research method with a descriptive approach which aims to describe and explain communication about infrastructure development in Situ Udik Village, as well as using phenomenological analysis techniques. This research determined 2 sources, namely the Village Secretary (Sekdes) and the Chair of the BPD. The results of this research show that the village government uses a strategy, namely prioritizing emergencies first and the media in conveying development messages is still small in scope, namely still conveying messages or information via WhatsApp groups. The Situ Udik Village Government has become a fairly good communicator in conveying development messages so that it has the impact of a development that is useful for the community and has become an independent village.